Computer Training for Students Traditional Islamic Boarding School - Saipul Wakit; Abdul Wahab; Tamaulina Br Sembirin Tamaulina; Nofirman Nofirman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Salaf Islamic boarding schools (traditional) are Islamic educational institutions that only focus on studying Islamic scholarship with the characteristics of yellow book-based learning. As for other sciences, it is not a priority in either the science or technology sector. Era 4.0 technology is an important element that must be mastered and followed by its development. There are many positive elements of the traditional Islamic boarding school system, but there are also shortcomings, including the lack of knowledge of science and technology, specifically the mastery of computer technology. In the midst of these problems, the researcher offers an activity that is problem-solving through community service activities and partnerships. Substantially, this activity focuses on increasing the knowledge and skills of partners in operating computers. The method in this activity is through several things, namely workshops, practices, discussions, tutorials, formation of study groups, mentoring, and evaluation after the activity. Practically, the results of this activity are 1) increased knowledge of partners regarding functions and components of computer software and hardware, 2) increased skills of partners in operating computers in MS word to create documents or complete work, 3) program sustainability at partner locations and groups learn to be independent.